Outcome Evaluation of Tribes Learning Communities in California, 2007-2010 - Hanson, Thomas L. ([Verlag nicht ermittelbar], 2012)
This study was an outcome evaluation that employed a group randomized experimental design to assess the effectiveness of a school-based violence prevention program known as Tribes in preventing youth violence. The study took place in elementary schools in the San Francisco Unified School District and targeted students in Kindergarten through Fifth grade. Within each school, teachers (and their students) were randomly assigned to the experimental condition, with teachers assigned to the intervention condition using Tribes in their classrooms and control teachers delivering usual lessons. Multiple, repeated measures, including teacher surveys and checklists, parent checklists, direct evaluator observations of classrooms, and individual student interviews were employed between May 2007 and November 2010. Researchers gathered data in four major outcome areas: classroom environment, teacher practices, and student behavior and reasoning.